Управління напруженістю систем за допомогою штучного інтелекту - Становський, Олександр Леонідович; Хомяк, Юрій Мефодійович; Торопенко, Алла Володимирівна; Науменко, Євгенія Олександрівна; Дадерко, Олеся Ігорівна (НТУ "ХПІ", 2017)
Показано, що рівнонапруженість систем, як стан, що забезпечує мінімальну вартість останніх, не може бути досягнений при звичайному проектуванні, оскільки внутрішні та зовнішні умови навантаження таких об’єктів цьому заважають. Розглянуто проблему створення смарт-систем, які за допомогою штучного інтелекту автоматично реагують на умови експлуатації та підлаштовуються під них, повертаючи при необхідності втрачену рівнонапруженість, а отже зберігають свою експлуатаційну надійність без нарощування зайвих витрат.

It is shown that the equilibrium of systems, as a state, providing the minimum cost of the latter, cannot be achieved in conventional design, since the internal and external conditions of such objects loading do not prevent this. A new notion of "uneven tension" as a numerical characteristic of the any complex object uneven resistance of the external environment influence was introduced, methods of its calculation were proposed, and the theorem on the coincidence of the minimum of uneven stress with the minimum cost of the object in the manufacture and operation. The system "EQUTENS" (equal tension support) for artificial (with the help of expert decisions) or unauthorized (with the help of an intellectual attractor) of adaptation of the object's characteristics to turbulent external loading during its operation, which restores the object state, returning it as much as possible to equilibrium of individual elements, is proposed. The problem of creation of smart systems, which with the help of artificial intelligence, automatically responds to the conditions of operation and adjusts to them, considering the lost voltage equilibrium if necessary, and therefore maintain their operational reliability without increasing the excess costs.
The systems tension control with the help of artificial intelligence
Keywords: смарт-система; рівнонапруженість; вартість мінімальна; надійність експлуатаційна; smart system; even tension; minimal cost; operational reliability